NAVIGATING THE DIGITAL MARKETPLACE: THE IMPACT OF E-COMMERCE AND SERVICE QUALITY ON ONLINE PURCHASE DECISIONS - Putri, Nastiti Yulisna; Lasiyono, Untung; Afkar, Taudlikhul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study reveals how e-commerce and service quality impact online purchase decisions among housewives. This study is motivated by the rapid growth of e-commerce, which has significantly changed purchasing dynamics and consumer behavior, especially among housewives, who play an essential role in purchasing decisions. The purpose of this study is to explore whether e-commerce and service quality have an impact on online purchasing decisions. The population in this study consisted of housewives in the Cerme sub-district in Gresik district - East Java. The population was sampled using the Cluster Random Sampling technique, so 239 respondents were used. The data analysis technique used is multiple linear regression. The results revealed that e-commerce and quality services together have a significant impact on online purchasing decisions. Further results show that consumer behavior variables also influence online purchasing decisions. Finally, this study has a significant relationship with the digital marketplace business and industry and recommendations for further research.